Osmanlı Devleti’nin Düzen Arayışı: Anayasal Düşünce Gelişiminin Dinamikleri / Ottoman State’s Quest for Order: Dynamics of Constitutional Thought Development - Tekin, Zeki; Okumuş, Gülnaz (Journal of History Culture and Art Research, 2018)
Abstract Mankind has put forth a special effort to ensure the order of society since the very beginning of it. The Ottoman State, has always ensured the public and social order like other Islamic states in the light of Allah's commandments. However, the present order started deteriorating due to dwindling basic principles (justice, merit, consultancy ...) with time which were imposed by the Shariah Law; to which the Ottoman Empire was subjected. The radical developments in the political, economic, social and legal fields that took place in Europe had affected the Ottoman State seriously like other states. Under the influence of all these internal and external dynamics, the Ottoman Empire started quest for a new order and attempted to bring a series of reforms under the name of westernization or modernization. Thus in the Ottoman State, besides these reform movements, the idea of creating a constitution had also emerged. This study tries to find out the internal and external dynamics in the formation of Kanun-ı Esasi which was the first constitution of the Ottoman Empire in the modern sense and the consequences of this quest for order. Öz İnsanoğlu, var olduğundan beri yaşadığı toplumun düzenini temin edebilmek için özel bir çaba göstermiştir. Kuruluşu itibariyle Ortaçağ devletlerinden olan Osmanlı Devleti, diğer İslam devletleri gibi kamu ve toplum düzenini her zaman Allah’ın hükümleri doğrultusunda tesis etmiştir. Ancak Osmanlının tâbi olduğu şer’i hukukun vaz ettiği temel prensiplerin (adalet, liyakat, meşveret…) zamanla göz ardı edilmesi ile mevcut düzen bozulmaya başlamıştır. Avrupa’da meydana gelen siyasal, ekonomik, toplumsal ve hukuk alanlarındaki köklü gelişmeler Osmanlı Devleti’ni ciddi anlamda etkilemiştir. Tüm bu iç ve dış dinamiklerin tesiriyle yeni düzen arayışına giren Osmanlı Devleti, batıcılık ya da modernleşme adı altında bir dizi reform teşebbüslerinde bulunmuştur. Osmanlı Devleti’nde bu reform hareketlerine paralel olarak bir anayasa oluşturma düşüncesi de böylece ortaya çıkmıştır. Bu çalışmada Osmanlının modern anlamda ilk anayasası olan Kanun-ı Esasi’nin oluşumuna kaynaklık eden iç ve dış dinamiklerin neler olduğu ve bunların tesirleri ortaya konulmaya çalışılmıştır.